A Pragmatic Study on Politeness in Classroom Discussion Among University Students - Desry Nurliana; Khairun Nisa; Sahfitri Ahwani; Nadila Adelia Putri; Siregar, Deasy Yunita (Universitas Negeri Medan, 2025)
A study on politeness strategies in classroom discussions highlights their role in fostering respectful and effective communication among university students. Using qualitative methods, the research observes a class of 30 students, focusing on verbal and non-verbal interactions during discussions. Four main politeness strategies are identified based on Brown and Levinson’s (1987) framework: positive politeness, negative politeness, off-record strategies, and bald on-record strategies. Positive politeness dominates in collaborative contexts, encouraging rapport and active participation, while negative politeness helps manage disagreements and maintain respect in hierarchical settings. Contextual factors such as cultural background, discussion topics, and classroom dynamics significantly influence the choice of strategies. Keywords: Politeness Strategy Classroom Discussion Pragmatic Communication Skills